Antibiotic Susceptibility Pattern of the Potential Pathogens of Ventilator Associated Pneumonia in the Endotracheal Tubes of Critically Ill Patients - Prabhat Kiran Khatri; Vikrant Negi; Naveen Kishoria; Namit Mathur; Vandana Sharma (Universitas Nahdlatul Ulama Surabaya, 2023)
An endotracheal (ET) tube offers surface for potential pathogens to attach and produce biofilm. These potential pathogens are typically hospital flora with a broad range of antibiotic resistance. The study aimed to characterize the biofilm-producing flora in ET tube of critically ill patients. Following extubation, ET tubes were retrieved aseptically from 100 different patients and promptly transported in a sterile ziplock bag. Each ET tube was cut into three different sections; inner lumen was scraped out and inoculated on Blood agar, MacConkey agar, and Chocolate agar. Colonies produced on media were tested for antibiotic susceptibility testing by applying disc diffusion and Colistin minimum inhibitory concentration (MIC). Out of 100 ET tubes, monomicrobial growth was observed in 62, polymicrobial growth in 14, and no growth in 24 specimens. A total of 93 potential pathogens were isolated including 25 (26.89%) Acinetobacter species, 23 (24.73%) Klebsiella species, 15(16.12%) Pseudomonas species, 13 (13.98%) E. coli, 6 (6.45%), Staphylococcus aureus, 4 (4.3%) Coagulase Negative Staphylococcus species (CoNS), 2 (2.15%) Proteus species, 1 (1.07%) Enterobacter species and 4 (4.3%) Candida species. Imipenem and Colistin proved to be among the most successful antibiotics against gram negative isolates. Only 1 out of 25 Acinetobacter species was resistant to Colistin. Methicillin resistance emerged in two S. aureus and three CoNS strains. Microorganisms usually adhere themselves to the surface of ET tubes. They may act as potential pathogens for the onset of Ventilator Associated Pneumonia (VAP) and are resistant to commonly administered antibiotics in hospitals. A technique to reduce or prevent the risk of biofilm development is crucial.